Investigating the combined effects of statins and exercise on skeletal muscle mitochondrial content and function, cardiorespiratory fitness and quality of life in individuals with dyslipidaemia: protocol for a randomised placebo-controlled trial - Simon Birk Kjær Jensen; Magni Mohr; Jacob Bejder; Nikolai B Nordsborg; Jacobina Kristiansen; Tórur Sjúrðarson; Jan Rasmussen; Helga Ellingsgaard; Steen Larsen; Sanna á Borg; Jørgen Martin Meinhardsson; Helgi Winther Olsen; et al. (BMJ Open)
Introduction Dyslipidaemia, affecting approximately 39% of adults worldwide, is a major risk factor for cardiovascular disease. Individuals with dyslipidaemia are often prescribed statins, which effectively lower plasma low-density lipoprotein cholesterol (LDL-C), thereby reducing the risk of cardiovascular events and mortality. Although statins lower LDL-C, emerging evidence suggests that they may counteract the beneficial adaptations to exercise in skeletal muscle mitochondria and whole-body aerobic capacity. The underlying mechanisms remain unclear, and there is a need for studies investigating how statins influence molecular adaptations to exercise. The primary objective of this study is to investigate the combined effects of statin therapy and focused exercise training on mitochondrial function and whole-body aerobic capacity in people with dyslipidaemia. The untargeted proteomic analysis will be incorporated to provide detailed insights into how statins may affect mitochondrial proteins and other muscle metabolic traits, offering molecular explanations for altered functional readouts at both the muscle and whole-body levels.Methods and analysis A total of 100 women and men (aged 40–65 years) diagnosed with dyslipidaemia without atherosclerotic cardiovascular disease will be enrolled in this 12-week, double-blinded, randomised, placebo-controlled trial. Participants will be randomised into one of four groups using a block randomisation approach to ensure an allocation ratio of 60:40 for exercise and non-exercise conditions, respectively. The four groups will be: (1) exercise+placebo, (2) exercise+atorvastatin (80 mg/day), (3) atorvastatin (80 mg/day) and (4) placebo. The primary outcome is mitochondrial function, measured by changes in skeletal muscle citrate synthase activity from baseline to post-intervention. Secondary outcomes include whole-body aerobic capacity (VO2peak) and proteomic analyses. Genetic analysis will be conducted to assess the role of genetic polymorphisms in individual responses to statins and exercise.Ethics and dissemination The trial has received ethical approval from the Faroe Islands Ethical Committee (2024-10) and adheres to the Declaration of Helsinki and General Data Protection Regulation (GDPR). Results will be published in peer-reviewed international journals.Trial registration number NCT06841536.